Analisis Faktor-Faktor yang Mempengaruhi Kualitas Auditor - Masnawaty Sangkala (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
In the business and industrial world, there are currently more possibilities to fill unfilled positions. The general public is currently quite interested in a career in public accounting. Professional guidance from a Public Accounting Firm (KAP) is one of them. Whether a professional KAP can occur depends greatly on the performance of the auditor. Auditor performance, especially the results of the work achieved by the auditor in carrying out his duties, is one of the benchmarks used to assess the good or bad of a job and his responsibilities. The writing style used is descriptive literature research, and the subject matter of the writing is related to the elements that affect the quality of the auditor. Where accountability indicators greatly improve the quality of audit work. If the auditor holds high standards of accountability, then professional care has a positive impact on the quality of the assessment results. This shows that the auditor will benefit greatly in determining the scope and method of audit work by using professional expertise and having sufficient confidence in the evidence found. Two factors, professional skepticism and sufficient confidence, can be used to measure professional care. Work experience also has a beneficial impact on audit quality. This shows that the audit made by Alim et al. higher quality and better quality as auditor experience and length of service increase.